Karakteristik Personal dalam Memoderasi Pengaruh Penganggaran Partisipatif dan Ambiguitas Peran pada Senjangan Anggaran - Dharmawan, Yoana; Wirakusuma, Made Gede (E-Jurnal Akuntansi; Vol 31 No 2 (2021)DO - 10.24843/EJA.2021.v31.i02.p08, 2021)
This study aims to determine the role of personal characteristics in moderating the effect of participatory budgeting on budgetary slack and to determine the role of personal characteristics in moderating the influence of role ambiguity on budgetary slack. Data used is primer data, the analysis technique used in this study is Moderated Regression Analysis. The results of the analysis address personal characteristics which weaken the effect of participatory budgeting on budgetary slack. This shows that with good personal characteristics, participatory budgets will be able to reduce budgetary slack events. Personal characteristics weaken the influence of role ambiguity on budgetary slack. This shows that good personal characteristics, the role ambiguity will be reduced and will able to reduce the budgetary slack. Keywords: Personal Characteristics; Participatory Budgeting; Role Ambiguity; Budgetary Slack.